CHANGE OF STRUCTURE AND COMPOSITION OF SURFACE LAYERS OF CONTACT SURFACES - Мнацаканов, Р. Г.; Довбуш, В. О.; Якобчук, О. Є. (Proceedings of National Aviation University (archive), 2021)
The results of researches of features of a structural condition of thin surface layers of metal at dynamic loading during boundary greasing with use of usual and chemically modified lubricants are considered. The conditions for the formation of the optimal structural composition, which determines the increase in wear resistance and the impact of the lubricating medium on the studied process.